Nanometer zinc oxide enhanced UV curing noctilucent ink and preparation method thereof

Through the preparation method of nano zinc oxide enhanced UV cured luminescent ink, the problems of complex preparation process and insufficient water resistance in the prior art are solved, and efficient and uniform luminescent effects and significant improvement in water resistance are achieved.

CN119177045AActive Publication Date: 2024-12-24DONGGUAN HAOCAI INK TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411484709.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The preparation process of existing UV cured polyurethane inks is complex and time-consuming, and the water resistance of the ink in high humidity environments is insufficient, and the production efficiency and performance need to be further optimized.

Method used

The preparation method of nano zinc oxide enhanced UV curing luminescent ink is adopted. The nano zinc oxide is coated with luminescent powder, combined with epoxy acrylic resin, polyester acrylic resin and acrylic acid ester, and 2-hydroxybenzophenone and photoinitiator are added. Ultrasonic dispersion and temperature regulation treatment significantly improve the curing speed and water resistance.

Benefits of technology

It greatly improves production efficiency, shortens the preparation time to about 6 hours, accelerates the curing speed, significantly improves water resistance, and makes the luminous effect more uniform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098432120000121
    Figure BDA0005098432120000121
Patent Text Reader

Abstract

The invention discloses nano-zinc oxide enhanced UV curing luminous ink and a preparation method thereof, and belongs to the technical field of ink, the nano-zinc oxide enhanced UV curing luminous ink comprises the following raw materials: 15-21 parts of nano-zinc oxide; 3.6 to 7.8 parts of 2-hydroxy benzophenone; 78 to 95 parts of isosorbide dimethyl ether; 18 to 27 parts of epoxy acrylic resin; 32 to 38 parts of polyester acrylic resin; 47 to 65 parts of acrylic ester; 17 to 23 parts of noctilucent powder; 0.6 to 1.2 parts of a defoaming agent; 0.8 to 2.1 parts of a dispersant; 1.4 to 1.8 parts of a leveling agent; and 0.6 to 0.9 part of a photoinitiator. The total preparation time is short, and the production efficiency is greatly improved; in addition, the curing speed is increased, and the water resistance is also remarkably improved; the dispersion rate of the noctilucent powder is improved in a manner of coating the nano zinc oxide with the noctilucent powder, so that the prepared nano zinc oxide enhanced UV curing noctilucent ink is more uniform in fluorescent effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inks, and in particular to a nano zinc oxide enhanced UV (ultraviolet light) curing luminous ink and a preparation method thereof. Background Art

[0002] UV ink has received extensive attention in recent years and has become one of the important materials in the printing industry due to its advantages such as no need for solvents, fast drying speed, good gloss, excellent water resistance and wear resistance. In the production of luminous signs, thermosetting luminous inks are traditionally used, but with the development of technology, UV luminous inks have gradually shown greater advantages, especially because of their faster curing speed, higher environmental protection and better physical properties, making them an ideal choice to replace thermosetting luminous inks. By adding luminescent powder to the ink, luminous ink can be prepared, which has a wide range of applications in the fields of luminous signs, special printed materials and safety signs.

[0003] For example, Chinese patent CN117327422B discloses a synthesis process of UV-curable polyurethane ink, in which hydrophilic and antibacterial imidazole salt functional groups and alkenyl functional groups are grafted onto the side chains of polyurethane, and the prepared imidazole salt-based polyurethane exhibits excellent UV light-curing properties. This material not only has a fast curing rate, but also uses water as a solvent, reflecting the advantages of green environmental protection. At the same time, through the chain extension reaction, the obtained polyurethane paint film has excellent water resistance, low water absorption, high hardness and strong adhesion. In addition, imidazole salt-based polyurethane also has good antibacterial properties, which makes it have broad application prospects in the fields of water-based inks and the like. This innovative synthesis process provides new ideas for the research and development of UV-curable inks, especially in application scenarios with high requirements for environmental protection and functionality, showing significant advantages.

[0004] However, despite the many advantages of the above process, its preparation process also has some limitations. For example, the reaction process is relatively complicated and takes at least 15 hours to complete, which is time-consuming and the production efficiency needs to be improved. In addition, although the UV-curable polyurethane ink prepared in the patent has good water resistance, in some special applications, especially in high humidity environments, the water resistance of the ink still has room for further optimization. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a nano zinc oxide enhanced UV curable luminous ink and a preparation method thereof.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] A nano zinc oxide enhanced UV curable luminous ink comprises the following raw materials in parts by weight: 15-21 parts of nano zinc oxide; 3.6-7.8 parts of 2-hydroxybenzophenone; 78-95 parts of isosorbide dimethyl ether; 18-27 parts of epoxy acrylic resin; 32-38 parts of polyester acrylic resin; 47-65 parts of acrylate; 17-23 parts of luminous powder; 0.6-1.2 parts of defoaming agent; 0.8-2.1 parts of dispersant; 1.4-1.8 parts of leveling agent; and 0.6-0.9 parts of photoinitiator.

[0008] A method for preparing the nano zinc oxide enhanced UV curable luminous ink comprises the following steps:

[0009] Step 1: Take luminous powder and nano zinc oxide, add them to isosorbide dimethyl ether, stir and react at room temperature, filter, wash and dry to obtain nano zinc oxide coated with luminous powder;

[0010] Step 2: adding epoxy acrylic resin, polyester acrylic resin and acrylate mixed with a dispersant to the nano zinc oxide coated with luminous powder, and stirring to obtain a dispersion;

[0011] Step 3: After ultrasonically dispersing the dispersion liquid, leveling agent, defoaming agent and 2-hydroxybenzophenone in step 2, the temperature is raised to 50-55°C, then lowered to 3-5°C and then raised to room temperature, a photoinitiator is added, and ultrasonic dispersion is continued;

[0012] Step 4: Filter to obtain nano zinc oxide enhanced UV curable luminous ink.

[0013] Furthermore, step one is specifically as follows: 17-23 parts of luminous powder and 15-21 parts of nano zinc oxide are added to 78-95 parts of isosorbide dimethyl ether, stirred at room temperature for 40-60 minutes, filtered, washed and dried to obtain nano zinc oxide coated with luminous powder.

[0014] Furthermore, step 2 is specifically as follows: adding 18-27 parts of epoxy acrylic resin, 32-38 parts of polyester acrylic resin and 47-65 parts of acrylate mixed with 0.8-2.1 parts of dispersant to the nano zinc oxide coated with luminous powder, and stirring for 10-25 minutes to obtain a dispersion.

[0015] Furthermore, step three is specifically as follows: ultrasonically disperse the dispersion of step two, 1.4-1.8 parts of leveling agent, 0.6-1.2 parts of defoaming agent, and 3.6-7.8 parts of 2-hydroxybenzophenone for 2-3 hours, heat to 50-55°C and keep warm for 20-30 minutes, reduce to 3-5°C and keep warm for 20-30 minutes, heat to room temperature, add 0.6-0.9 parts of photoinitiator, and continue ultrasonic dispersion for 1-1.5 hours.

[0016] Furthermore, the filter pore diameter during filtering in step 4 is 80-100 μm.

[0017] Furthermore, the leveling agent is selected from one or more of BYK333, TEGO450 or LGH7499 leveling agents.

[0018] Furthermore, the dispersant is TEGODispers 685 or TEGODispers 688.

[0019] Furthermore, the particle size of the luminous powder is 50-60 μm.

[0020] Furthermore, the particle size of the nano zinc oxide is 40-50nm.

[0021] Compared with the prior art, the present invention has the following beneficial effects: the total preparation time of the present invention is short (the whole process is about 6 hours), which greatly improves the production efficiency; in addition, the present invention accelerates the curing speed, and the water resistance is also significantly improved; the dispersion rate of the luminous powder is increased by coating the nano zinc oxide with the luminous powder, so that the fluorescent effect of the prepared nano zinc oxide enhanced UV curing luminous ink is more uniform. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1: This embodiment provides a method for preparing a nano zinc oxide enhanced UV curable luminous ink, comprising the following steps:

[0024] Step 1: Take 23 parts of luminous powder and 21 parts of nano zinc oxide, add them to 95 parts of isosorbide dimethyl ether, stir and react at room temperature at a speed of 500 rpm for 60 minutes, filter, wash and dry to obtain nano zinc oxide coated with luminous powder;

[0025] Step 2: Add 27 parts of epoxy acrylic resin, 38 parts of polyester acrylic resin and 65 parts of acrylate mixed with 2.1 parts of dispersant to the nano zinc oxide coated with luminous powder, and stir for 25 minutes to obtain a dispersion;

[0026] Step 3: ultrasonically disperse the dispersion of step 2, 1.8 parts of leveling agent, 1.2 parts of defoamer, and 7.8 parts of 2-hydroxybenzophenone for 3 hours, heat to 50°C and keep warm for 30 minutes, reduce to 5°C and keep warm for 30 minutes, heat to room temperature, add 0.9 parts of photoinitiator, and continue ultrasonic dispersion for 1.5 hours;

[0027] The leveling agent is BYK333;

[0028] The defoamer is GPES type defoamer;

[0029] The dispersant is TEGODispers 685;

[0030] The particle size of the luminous powder is 60 μm;

[0031] The particle size of the nano zinc oxide is 50nm;

[0032] The luminous powder is selected from existing commercially available products, such as the rare earth luminous powder (long afterglow luminous powder) disclosed in Chinese patent CN103254663B;

[0033] Step 4: Pass through a 100 μm filter membrane to obtain nano zinc oxide enhanced UV curable luminous ink.

[0034] The nano zinc oxide enhanced UV curing luminous ink prepared by the invention has a hardness of 5H, which meets the industry standard.

[0035] Embodiment 2: This embodiment provides a method for preparing a nano zinc oxide enhanced UV curable luminous ink, comprising the following steps:

[0036] Step 1: Take 17 parts of luminous powder and 15 parts of nano zinc oxide, add them to 78 parts of isosorbide dimethyl ether, stir and react at room temperature at a speed of 500 rpm for 40 minutes, filter, wash and dry to obtain nano zinc oxide coated with luminous powder;

[0037] Step 2: Add 18 parts of epoxy acrylic resin, 32 parts of polyester acrylic resin and 47 parts of acrylate mixed with 0.8 parts of dispersant to the nano zinc oxide coated with luminous powder, and stir for 10 minutes to obtain a dispersion;

[0038] Step 3: ultrasonically disperse the dispersion of step 2, 1.4 parts of leveling agent, 0.6 parts of defoamer and 3.6 parts of 2-hydroxybenzophenone for 2 hours, heat to 55°C and keep warm for 20 minutes, reduce to 3°C and keep warm for 20 minutes, heat to room temperature, add 0.6 parts of photoinitiator, and continue ultrasonic dispersion for 1 hour;

[0039] The leveling agent is LGH7499 leveling agent;

[0040] The defoamer is GPES type defoamer;

[0041] The dispersant is TEGODispers 688;

[0042] The particle size of the luminous powder is 50 μm;

[0043] The particle size of the nano zinc oxide is 40 nm;

[0044] Step 4: Pass through an 80 μm filter membrane to obtain nano zinc oxide enhanced UV curable luminous ink.

[0045] Embodiment 3: This embodiment provides a method for preparing a nano zinc oxide enhanced UV curable luminous ink, comprising the following steps:

[0046] Step 1: Take 20 parts of luminous powder and 18 parts of nano zinc oxide, add them to 85 parts of isosorbide dimethyl ether, stir and react at room temperature at a speed of 500 rpm for 52 minutes, filter, wash and dry to obtain nano zinc oxide coated with luminous powder;

[0047] Step 2: Add 21 parts of epoxy acrylic resin, 35 parts of polyester acrylic resin and 58 parts of acrylate mixed with 1.4 parts of dispersant to the nano zinc oxide coated with luminous powder, and stir for 21 minutes to obtain a dispersion;

[0048] Step 3: ultrasonically disperse the dispersion of step 2, 1.5 parts of leveling agent, 1.1 parts of defoamer, and 5.6 parts of 2-hydroxybenzophenone for 2.5 hours, heat to 52°C and keep warm for 25 minutes, reduce to 4°C and keep warm for 22 minutes, heat to room temperature, add 0.8 parts of photoinitiator, and continue ultrasonic dispersion for 1 hour;

[0049] The leveling agent is TEGO450 leveling agent;

[0050] The defoamer is GPES type defoamer;

[0051] The dispersant is TEGODispers 685;

[0052] The particle size of the luminous powder is 54 μm;

[0053] The particle size of the nano zinc oxide is 42nm;

[0054] Step 4: Pass through a 90 μm filter membrane to obtain nano zinc oxide enhanced UV curable luminous ink.

[0055] Comparative Example 1:

[0056] The difference between this comparative example and Example 3 is that in step 3, the temperature is not lowered to 4°C and then raised, but directly lowered to room temperature;

[0057] This embodiment provides a method for preparing a nano zinc oxide enhanced UV curable luminous ink, comprising the following steps:

[0058] Step 1: Take 20 parts of luminous powder and 18 parts of nano zinc oxide, add them to 85 parts of isosorbide dimethyl ether, stir and react at room temperature at a speed of 500 rpm for 52 minutes, filter, wash and dry to obtain nano zinc oxide coated with luminous powder;

[0059] Step 2: Add 21 parts of epoxy acrylic resin, 35 parts of polyester acrylic resin and 58 parts of acrylate mixed with 1.4 parts of dispersant to the nano zinc oxide coated with luminous powder, and stir for 21 minutes to obtain a dispersion;

[0060] Step 3: Stir the dispersion of step 2, 1.5 parts of leveling agent, 1.1 parts of defoamer, and 5.6 parts of 2-hydroxybenzophenone for 2.5 hours, heat to 52°C and keep warm for 25 minutes, cool to room temperature, add 0.8 parts of photoinitiator, and continue stirring for 1 hour;

[0061] The leveling agent is TEGO450 leveling agent;

[0062] The defoamer is GPES type defoamer;

[0063] The dispersant is TEGODispers 685;

[0064] The particle size of the luminous powder is 54 μm;

[0065] The particle size of the nano zinc oxide is 42nm;

[0066] Step 4: Pass through a 90 μm filter membrane to obtain nano zinc oxide enhanced UV curable luminous ink.

[0067] Comparative Example 2:

[0068] This comparative example differs from Example 3 in that 2-hydroxybenzophenone is not added;

[0069] This embodiment provides a method for preparing a nano zinc oxide enhanced UV curable luminous ink, comprising the following steps:

[0070] Step 1: Take 20 parts of luminous powder and 18 parts of nano zinc oxide, add them to 85 parts of isosorbide dimethyl ether, stir and react at room temperature at a speed of 500 rpm for 52 minutes, filter, wash and dry to obtain nano zinc oxide coated with luminous powder;

[0071] Step 2: Add 21 parts of epoxy acrylic resin, 35 parts of polyester acrylic resin and 58 parts of acrylate mixed with 1.4 parts of dispersant to the nano zinc oxide coated with luminous powder, and stir for 21 minutes to obtain a dispersion;

[0072] Step 3: ultrasonically disperse the dispersion of step 2, 1.5 parts of leveling agent and 1.1 parts of defoamer for 2.5 hours, heat to 52°C and keep warm for 25 minutes, reduce to 4°C and keep warm for 22 minutes, heat to room temperature, add 0.8 parts of photoinitiator, and continue ultrasonic dispersion for 1 hour;

[0073] The leveling agent is TEGO450 leveling agent;

[0074] The defoamer is GPES type defoamer;

[0075] The dispersant is TEGODispers 685;

[0076] The particle size of the luminous powder is 54 μm;

[0077] The particle size of the nano zinc oxide is 42nm;

[0078] Step 4: Pass through a 90 μm filter membrane to obtain UV-curable luminous ink.

[0079] Comparative Example 3:

[0080] The difference between this comparative example and Example 3 is that in step 3, the temperature is not lowered to 4°C and then raised, but directly lowered to room temperature and 2-hydroxybenzophenone is not added;

[0081] This embodiment provides a method for preparing a nano zinc oxide enhanced UV curable luminous ink, comprising the following steps:

[0082] Step 1: Take 20 parts of luminous powder and 18 parts of nano zinc oxide, add them to 85 parts of isosorbide dimethyl ether, stir and react at room temperature at a speed of 500 rpm for 52 minutes, filter, wash and dry to obtain nano zinc oxide coated with luminous powder;

[0083] Step 2: Add 21 parts of epoxy acrylic resin, 35 parts of polyester acrylic resin and 58 parts of acrylate mixed with 1.4 parts of dispersant to the nano zinc oxide coated with luminous powder, and stir for 21 minutes to obtain a dispersion;

[0084] Step 3: Stir the dispersion of step 2, 1.5 parts of leveling agent and 1.1 parts of defoamer for 2.5 hours, heat to 52°C and keep warm for 25 minutes, cool to room temperature, add 0.8 parts of photoinitiator, and continue stirring for 1 hour;

[0085] The leveling agent is TEGO450 leveling agent;

[0086] The defoamer is GPES type defoamer;

[0087] The dispersant is TEGODispers 685;

[0088] The particle size of the luminous powder is 54 μm;

[0089] The particle size of the nano zinc oxide is 42nm;

[0090] Step 4: Pass through a 90 μm filter membrane to obtain nano zinc oxide enhanced UV curable luminous ink.

[0091] Experimental Example: The performance of the nano zinc oxide enhanced UV curable luminous ink prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the results were as follows:

[0092] The UV curable luminous ink is light-cured in a UV curing machine by spraying, and the curing time is recorded;

[0093] Sample preparation: 75mm×150mm sample;

[0094] Number of samples: 3 samples are prepared for each group, and the data are averaged; select a suitable substrate (glass sheet), the surface of the substrate should be smooth, clean, free of oil or other contaminants, the size of the substrate should not be smaller than the sample size, and use isopropyl alcohol cleaner to thoroughly clean the surface of the substrate to ensure that there is no residue before spraying.

[0095] Curing conditions: The linear power of the curing light source is 200W / cm, and the ink thickness is 15 microns;

[0096] Water tank: A corrosion-resistant water tank should be used, and the water in the tank can completely cover the specimen;

[0097] Constant temperature water bath device: equipped with a constant temperature control system to keep the water temperature in the water tank within the temperature range required by the test (such as 38±1℃).

[0098] Bracket: used to fix the specimen vertically or horizontally in the water tank so that it is completely immersed in water;

[0099] Temperature control: Control the water temperature in the water tank at 38±1℃ and ensure that the temperature remains constant throughout the test;

[0100] Immersion time: According to ASTM D870-2002, the immersion time is 24 hours;

[0101] Water quality requirements: Use deionized water to avoid impurities or chemicals in the water that may affect the test results;

[0102] Test steps:

[0103] Specimen fixation: Fix the cured UV light-curing resin film specimen vertically or horizontally on the bracket, ensuring that the specimen is completely immersed in water and does not touch the bottom of the water tank.

[0104] Water immersion: Place the rack with the sample in a constant temperature water bath, start timing, ensure that the water temperature is stable at 38±1℃, and that the water completely covers the sample;

[0105] Regular inspection: After the specified immersion time, take out the sample and immediately inspect its appearance and performance;

[0106] Result evaluation:

[0107] Appearance observation: Observe whether there are bubbles, peeling, cracking, expansion or discoloration on the surface of the sample;

[0108] Performance test: Perform performance test on the sample after immersion;

[0109] Prepare the sample according to GB / T 13217.1, scrape the sample and place it for 24 hours; stick the tape on the ink printed surface (the tape coverage position does not include the edge of the ink printed sample), roll it back and forth on the adhesive tape roller for 3 times, place it for 5 minutes, clamp the sample on the A plate, fix the exposed tape on the B plate, then turn on the machine, and rotate the A plate at a speed of 0.6~~1.0m / s to peel off the tape.

[0110] A(%)=A1 / (A1+A2)*100%

[0111] A: Ink adhesion fastness

[0112] A1: Number of grids in the ink layer

[0113] A2: Number of cells of the ink layer to be peeled off

[0114] Change in adhesion strength: A (before immersion) - A (after immersion)

[0115]

[0116] The change in adhesion fastness before and after immersion is significantly improved, indicating that the water resistance of Comparative Example 1-2 is reduced;

[0117] The total preparation time of the present invention is short (the whole process is about 6 hours), which greatly improves the production efficiency; in addition, through the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the present invention accelerates the curing speed by adding 2-hydroxybenzophenone and step three, and the water resistance is also significantly improved; the dispersion rate of the luminous powder is increased by coating the nano zinc oxide with the luminous powder, so that the fluorescent effect of the prepared nano zinc oxide enhanced UV curing luminous ink is more uniform.

[0118] 2-Hydroxybenzophenone is a widely used UV absorber. When 2-Hydroxybenzophenone is added to UV light-curing resins, the materials may have the following major effects: Enhanced UV resistance: UV shielding: 2-Hydroxybenzophenone can absorb the UV-A and UV-B bands in the UV spectrum, playing a role in shielding UV rays. This helps protect the light-curing resin from degradation under long-term exposure to sunlight or other UV sources, thereby extending the service life of the material. Improved light stability: By absorbing UV rays, 2-Hydroxybenzophenone reduces the damage of UV rays to the resin molecular chain, prevents the resin from photodegradation or yellowing, and improves the light stability of the material. Impact on the photocuring process: Possible reduction in curing rate: Due to the UV absorption properties of 2-Hydroxybenzophenone, it may absorb part of the UV light used to initiate the photocuring reaction, thereby reducing the amount of light reaching the photoinitiator, which may lead to a slower rate of photocuring reaction. Weather resistance may also have a positive effect due to its absorption of UV rays. Changes in optical properties: The introduction of 2-Hydroxybenzophenone may slightly affect the transparency or color of the resin. In the present invention, Comparative Examples 1-3 also confirm that the addition of 2-hydroxybenzophenone alone does have a negative effect on the photocuring speed.

[0119] However, in the present invention, the main effect of adding 2-hydroxybenzophenone is to accelerate the curing speed and improve the water resistance, which may be due to: the sensitization effect of 2-hydroxybenzophenone: the synergistic effect of energy transfer and photoinitiator: in the scheme of the present invention, 2-HBP is added to the photocurable resin system and subjected to ultrasonic dispersion and temperature regulation. As a UV absorber, 2-HBP may transfer the absorbed energy to the photoinitiator by energy transfer after absorbing UV light. Since the absorption spectrum of the photoinitiator may overlap with that of 2-HBP, the energy transfer effect may cause the photoinitiator to be excited faster, generate more free radicals, and thus accelerate the curing speed. Potential photoinitiator activity: although 2-HBP is usually used as a UV absorber, under certain conditions, 2-HBP may generate some active intermediates after absorbing UV light, and these intermediates may have the ability to initiate free radical reactions. Through ultrasonic dispersion and temperature regulation, the photoinitiator effect of 2-HBP may be enhanced, further accelerating the photocuring speed. Uniform dispersion improves photoinitiator efficiency: In the scheme of the present invention, the ultrasonic dispersion process significantly increases the uniformity of the system, especially the interaction between 2-HBP and the photoinitiator is more sufficient. This may make the photoinitiator absorb ultraviolet light more uniformly throughout the system, reduce the phenomenon of local photoinitiator oversaturation or deficiency, and thus accelerate the overall curing speed. Thermosensitive effect enhances the reaction rate: The temperature change mentioned in the step (raising the temperature to 50°C, then dropping to 4°C, and finally raising to room temperature) may affect the photochemical reaction kinetics of 2-HBP. The change in temperature may optimize the binding state or energy transfer efficiency of 2-HBP and the photoinitiator, especially at 50°C, 2-HBP may be in an efficient energy transfer or activation state, thereby accelerating the curing reaction. Spectral regulation effect: The introduction of 2-HBP may change the overall optical properties of the resin system, such as changing the refraction or reflection characteristics of light, so that more ultraviolet light effectively acts on the photoinitiator. This change may lead to an increase in the excitation efficiency of the photoinitiator, thereby accelerating the curing speed.

[0120] In addition, in terms of water resistance, neither the special temperature change program nor the addition of 2-hydroxybenzophenone alone has a significant effect. When both are present in the program, the water resistance of the resin is significantly improved. The reasons may be: The effect of temperature on 2-HBP: The molecular structure and polar groups (such as hydroxyl and carbonyl) of 2-HBP may exhibit different physicochemical behaviors at different temperatures. When the temperature rises to 50°C, the 2-HBP molecules may be more active or have a higher solubility, making them more evenly dispersed in the resin matrix and may form stronger intermolecular interactions with the resin molecules. The effect of low-temperature curing: The process of cooling to 4°C may promote a more orderly arrangement of 2-HBP in the resin network or a more dense embedding of the resin matrix. At low temperatures, the molecular motion slows down, and 2-HBP may form more stable interactions (such as hydrogen bonds or van der Waals forces) in the resin matrix, thereby improving the density of the material. Temperature regulation promotes the increase of crosslinking density: Special temperature changes may affect the crosslinking reaction rate and mode of the resin. At high temperatures (50°C), the reaction rate is accelerated, which may result in a looser initial crosslinking of the resin. When the temperature drops rapidly to 4°C, the resin molecules may become more compact due to low-temperature curing, forming a denser network structure. The subsequent process of heating to room temperature may further solidify and stabilize the resin network, and the final cross-linked network formed is more uniform and stable. This dense network helps to improve water resistance. Effect of temperature change on the interaction between 2-HBP and resin: 2-HBP may interact differently with the resin matrix during temperature change. When the temperature rises, 2-HBP may be more easily dispersed or dissolved in the resin, and rearranged when the temperature drops. This process may promote the uniform distribution of 2-HBP in the resin network, thereby enhancing its strengthening effect on the resin. Generation of synergistic effect: Optimization of multiple interactions: When 2-HBP is combined with temperature change, a synergistic effect may be generated, that is, the physical and chemical properties of 2-HBP at different temperatures and the cross-linking reaction of the resin produce a more favorable interaction. 2-HBP enhances its interaction with the resin at high temperature and further stabilizes this interaction at low temperature, making the final cross-linked network more dense and stable, thereby significantly improving water resistance. Molecular dynamics regulation: Temperature changes may change the molecular dynamics environment of the resin, especially during the cross-linking reaction, the rate of molecular motion and the reaction path may be adjusted to a state that is more conducive to the formation of a highly dense cross-linked network. In this process, 2-HBP may further improve the water resistance of the cured resin by stabilizing the intermediate reaction state or promoting the selection of a specific reaction path. Improvement of molecular arrangement and density: Specific temperature changes may prompt 2-HBP molecules to form a more ordered or denser arrangement in the resin matrix, thereby reducing microscopic voids or defects. This structural optimization reduces the path and space for water molecules to penetrate, significantly improving the water resistance of the material.Internal stress release and structural stability: Temperature cycling may help release the internal stress generated during the resin curing process, resulting in a more stable internal structure. The presence of 2-HBP may further help optimize this structural stability and ensure the durability of the material in an aqueous environment.

[0121] In conclusion, when 2-hydroxybenzophenone is used in combination with a specific temperature change, the water resistance of UV-curable resins may be significantly improved through a synergistic effect. This synergistic effect may come from the changes in the molecular behavior of 2-HBP at different temperatures, the optimization of the cross-linking network, the enhancement of intermolecular interactions, and the densification of the microstructure. The temperature change may cause 2-HBP to embed more effectively into the resin network and form a denser and more ordered structure, thereby significantly improving the water resistance of the resin coating.

[0122] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nano zinc oxide enhanced UV curable luminous ink, characterized in that: The invention comprises the following raw materials in parts by weight: 15-21 parts of nano zinc oxide; 3.6-7.8 parts of 2-hydroxybenzophenone; 78-95 parts of isosorbide dimethyl ether; 18-27 parts of epoxy acrylic resin; 32-38 parts of polyester acrylic resin; 47-65 parts of acrylate; 17-23 parts of luminous powder; 0.6-1.2 parts of defoaming agent; 0.8-2.1 parts of dispersing agent; 1.4-1.8 parts of leveling agent; and 0.6-0.9 parts of photoinitiator.

2. A method for preparing the nano zinc oxide enhanced UV curable luminous ink as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Take luminous powder and nano zinc oxide, add them to isosorbide dimethyl ether, stir and react at room temperature, filter, wash and dry to obtain nano zinc oxide coated with luminous powder; Step 2: adding epoxy acrylic resin, polyester acrylic resin and acrylate mixed with a dispersant to the nano zinc oxide coated with luminous powder, and stirring to obtain a dispersion; Step 3: After ultrasonically dispersing the dispersion liquid, leveling agent, defoaming agent and 2-hydroxybenzophenone in step 2, the temperature is raised to 50-55°C, then lowered to 3-5°C and then raised to room temperature, a photoinitiator is added, and ultrasonic dispersion is continued; Step 4: Filter to obtain nano zinc oxide enhanced UV curable luminous ink.

3. The preparation method according to claim 2, characterized in that: Step 1 is specifically as follows: 17-23 parts of luminous powder and 15-21 parts of nano zinc oxide are added to 78-95 parts of isosorbide dimethyl ether, stirred at room temperature for 40-60 minutes, filtered, washed and dried to obtain nano zinc oxide coated with luminous powder.

4. The preparation method according to claim 3, characterized in that: Step 2 is specifically as follows: adding 18-27 parts of epoxy acrylic resin, 32-38 parts of polyester acrylic resin and 47-65 parts of acrylate mixed with 0.8-2.1 parts of dispersant to the nano zinc oxide coated with luminous powder, and stirring for 10-25 minutes to obtain a dispersion.

5. The preparation method according to claim 4, characterized in that: Step three is specifically as follows: ultrasonically disperse the dispersion of step two, 1.4-1.8 parts of leveling agent, 0.6-1.2 parts of defoaming agent, and 3.6-7.8 parts of 2-hydroxybenzophenone for 2-3 hours, heat to 50-55°C and keep warm for 20-30 minutes, reduce to 3-5°C and keep warm for 20-30 minutes, heat to room temperature, add 0.6-0.9 parts of photoinitiator, and continue ultrasonic dispersion for 1-1.5 hours.

6. The preparation method according to claim 5, characterized in that: The filter pore diameter during step 4 filtration is 80-100 μm.

7. The preparation method according to claim 6, characterized in that: The leveling agent is selected from one or more of BYK333, TEGO450 or LGH7499 leveling agents.

8. The preparation method according to claim 7, characterized in that: The dispersant is TEGODispers 685 or TEGODispers 688.

9. The preparation method according to claim 8, characterized in that: The particle size of the luminous powder is 50-60 μm.

10. The preparation method according to claim 9, characterized in that: The particle size of the nano zinc oxide is 40-50nm.

Citation Information

Patent Citations

  • Grafted and modified rare earth noctilucent powder, its preparation method and application

    CN103254663B

  • A synthesis process of UV curing polyurethane ink

    CN117327422B

  • UV (ultraviolet)-curable luminous printing ink for gravure printing and method for preparing UV-curable luminous printing ink

    CN106810939A

  • UV light solidified luminous printing ink

    CN1657575A

  • Superhydrophobic UV curable coating

    US20180134904A1